A laboratory based intervention to improve appropriateness of lipid tests and audit cholesterol lowering in primary care. Issue 7323 (24th November 2001) - Smellie, W Stuart A; Lowrie, Ruth; Wilkinson, Emma
Abstract: Problem: A need exists to reduce inequalities in lipid testing, to provide relevant, individual, patient based interpretation for users, and to audit lipid lowering in primary care. Design: Model to compare laboratory activity between different general practices; construction of computer based strategies to define the lipid tests to be done and to interpret results for primary and secondary coronary prevention patients; introduction of the strategies into routine use; monitoring of any change after the intervention; and investigation of the potential of the strategies to produce audit data for primary care groups. Background and setting: Hospital clinical laboratory serving 22 general practices covering 150 000 patients in Bishop Auckland area County Durham. Key measurements for improvement: Reduction in differences in testing for the different serum lipids in coronary prevention. Production of usable audit data for the primary care groups involved. Strategies for change: Four different categories of coronary prevention patient, with, for each category, the defined lipid tests to be done and advice to be given (based on the results), using the computer based strategies. Effects of change: Standardised test activity and the qualitative profile of the tests performed changed significantly. The strategies were readily adopted (median use 78%) within six months of introduction. Lessons learnt: Computer based strategies can correct qualitative and quantitative differences in test requesting, provide interpretative guidance in accordance with national guidelines, and offer a cost effective model to monitor results of cholesterol lowering in general practice.